32 Image not imagine. pocus and discharge decision making in hospitalized patients with heart failure. (30th September 2020) - O'Toole, L; Sharma, P; Malik, M; Rummun, S; Fleming, S
Abstract : Introduction: Among patients hospitalized with heart failure (HF), residual congestion (RC) at discharge is common and predicts rehospitalization and death at 6 months. Clinical assessment of congestion is challenging particularly for hospitalized patients as they near discharge. Point of Care Ultrasound (POCUS) is an emerging modality offering advantages of accessibility and convenience over traditional imaging techniques and can be used to assess pulmonary congestion and volume status at the bedside. Aims: To describe the reproducibility of lung POCUS when performed by an experienced echocardiographer, and the accuracy of assessments performed by novice practitioners. To explore the clinical usefulness of POCUS in the management of hospitalized patients with HF, who are judged as clinically euvolemic following inpatient therapy and for whom discharge is under consideration. Method: We performed POCUS of the lungs at the bedside for sequential inpatients with HF. The index exam was performed on the day in which the patient was judged clinically to be euvolemic. Based on this exam patients were separated into residual congestion (RC) and true euvolemic (TEu) groups. Each patient had at least 1 POCUS exam, RC group patients had further studies during their stay. The POCUS exam consisted of: imaging the lung bases for pleural fluid, 8 lung zones anteriorly for B-lines, and established IVC indices. All exams were done first by a single experienced echocardiographer. To obtain a measure of reproducibility, 120 stored loops were analysed blindly and independently by each author. We collected baseline demographic clinical and laboratory data, time to discharge from index POCUS, and readmission rates for all patients. For those in the RC group we report further in-hospital weight loss, and any adverse events occurring from further treatment. Results: Intraobserver reproducibility for assessment of pleural fluid and B-lines were 100% and 98% respectively. Novice practitioners reported presence/absence of pleural fluid and B-lines with an accuracy of 97% and 96% respectively. 17 sequential patients were recruited over 6 weeks. 9 patients were judged to have RC at the time of POCUS. These 9 form the RC group, the remaining 8 form the TEu group. Median age of the total group was 79 (IQR 70–83), 10/19 had HF with reduced EF, median peak NT-proBNP taken during the index admission was 4399 (IQR 3162–6575). Corresponding figures for groups were RC: age 75 (IQR 71–79), 5/9 HFrEF, and peak NT-proBNP 5530 (IQR 3653–8300); TEu age 81 (IQR 68–83), 4/8 HFrEF, and peak NT-proBNP 4010 (IQR 1671–4399). Median additional LOS for the RC group was 4 days (IQR 3–7). 7/8 TEu patients were discharged within 1 day of the index POCUS confirming euvolemia. No patient in either group was readmitted at 30 days. RC group patients had additional therapy under POCUS guidance with the aim of eliminating residual pulmonary congestion. An additional median weight loss of 4.8Kg (IQR 3.4–6.5Kg) was achieved. 1 RC group patient had an episode of hypotension requiring fluid replacement. 2 had residual pulmonary congestion persistent on discharge. No patient had a rise of serum creatinine greater than 50% from baseline. Conclusion: In this pilot study we show that RC is common in hospitalized patients with HF who are judged clinically to be euvolemic. We show that POCUS can provide a reproducible and clinically relevant assessment of RC and that this information can be used to guide further management.